A Randomized-Controlled Trial of Mentalization-Based Treatment Compared With Structured Case Management for Borderline Personality Disorder in a Mainstream Public Health Service - Carlyle, Dave; Green, Robert; Inder, Maree; Porter, Richard; Crowe, Marie; Mulder, Roger; Frampton, Chris (Frontiers in Psychiatry, 2020)
Background: Treatment of borderline personality disorder (BPD) in publicly funded mental health services generally use approaches based on medical interventions and generic case management. Specific psychological therapies developed for BPD may be more effective but have rarely been evaluated in routine clinical practice. Aim: To examine the effectiveness of Mentalization Based Treatment (MBT) in adults with an established diagnosis of BPD under the care of a publicly funded Mental Health Service (MHS), on rates of non-suicidal self-harm (NSSH) and attempted suicide (SA). Methods: A randomised, controlled trial (RCT) comparing 18 months of MBT with Enhanced Therapeutic Case Management (ETCM), a form of Structured Clinical Case Management (ICTRP: ACTRN12612000951853). Participants were adults recruited from a patient population under the care of a publicly funded mental health service (MHS) with a confirmed diagnosis of BPD. The primary outcome measures were the incidence of non-suicidal self-harm or suicide attempt over 18 months of treatment. Results: 72 participants (71 females, 1 male) were randomised to MBT (n = 38) or ETCM (n = 34). Both groups showed a significant reduction in the overall incident rate of SA and NSSH. Between groups, SA rates were higher in the MBT group and conversely NSSH rates were higher in the ECTM group Conclusions: The introduction of a structured service that delivered a structured psychotherapy (MBT) and an effective case management approach (ETCM) both resulted in improvements in SA and NSSH. The differences in improvements found between groups within this study setting will require further research.